Optimization of Posyandu Cadre Role and Maternal Education in the Prevention of Stunting: An Integrated Community-Based Approach - Sanggelorang, Yulianty; Anggela, Jelsy; Katanga, Sefanya (BKM Public Health and Community Medicine, 2024)
Purpose: This community service initiative was designed to enhance knowledge of stunting among mothers with toddlers and pregnant women as well as to train Posyandu (Integrated Health Service Post) cadres in accurate anthropometric measurements as a preventive measure against stunting. Content: The program was executed through educational and training sessions at the Wineru Village Hall, Likupang Timur District, North Minahasa Regency, on January 30, 2024. The educational session targeted mothers with toddlers and pregnant women, while the training focused on anthropometric measurement for Posyandu cadres, who hold a pivotal role in child care in Indonesia. The program was culminated in the distribution of Supplementary Food (PMT), including biscuits, milk, and snacks, to all participants. The program’s efficacy was assessed through pre- and post-tests administered to the mothers and an evaluation of the Posyandu cadres adherence to athropometric measurement procedures. Paired t-test analysis indicated a significant increase in maternal knowledge following the educational session (p< 0.05). The assessment of measurement practices demonstrated that all cadres performed anthropometric measurements in accordance with the correct protocols. These educational and training sessions was proven effective in enhancing mothers and pregnant women’s knowledge of stunting and cadre skills concerning stunting prevention, as evidenced by the significant improvements in pre- and post-test results and the cadres’ compliance with anthropometric measurement procedures. This program also successfully elevated awareness and imparted essential skills for stunting prevention within the community. Additionally, the analysis indicated that community-based interventions can significantly contribute to reducing stunting prevalence.